Applying Reciprocal Teaching to Overcome Learners' Barriers to Effective Listening - Hesti Rokhaniyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The research is the action research aimed at investigating to what extent Reciprocal Teaching overcomes learners’ barriers to effective listening and identifying the situation of teaching and learning when Reciprocal Teaching is employed. Several techniques: interview, observation, and test were applied to obtain the data. The mean score of two raters was calculated to derive the qualitative data; Constant Comparative Method was implemented to analyze the qualitative data. The research result showed Reciprocal Teaching implementation could overcome learners’ barrier to listening including detecting the keywords; recognizing grammar and vocabularies; and discriminating distinctive sounds. The enhancement of Reciprocal Teaching illustrated form mean score of pre-test was 37.4; post-test 1 was 70.4; and post-test 2 was 81. The use of Reciprocal Teaching also optimized the class situation: learners felt encouraged to be receptive to communication in active listening; they got freedom to mind their ideas; and they were more engaged to do mutual task. Considering the finding of the research, the lectures are recommended to use this research for guiding heir learners to solve listening barrier through Reciprocal Teaching.